KAJIAN PEMELIHARAAN BANGUNAN GEDUNG LPMP PROVINSI ACEH - Fadli Fadli; Muttaqin Muttaqin; Mochammad Afifuddin (Prodi Magister Teknik Sipil Unsyiah, 2018)
Lembaga Penjaminan Mutu Pendidikan (LPMP) of Aceh Province is a technical service. Education and Culture Ministry in Aceh is not technical service which result in understanding of the importance of building maintenance is still minimum. The problem in this research is to review the existing condition of the buildings in LPMP Unit 1 of Aceh Province, the organizational structure and define the scope of maintenance on The existing Buildings of LPMP Unit 1 of Aceh province. From the results obtained, for work program Standard operational procedure that has been owned by the Agency is still not appropriate this is directly related to unavailable of technical guidelines, it is in accordance with the opinion of respondents, which 70% answered The Unavailable of Standard Operational Procedure. On financing whether funds from the government are high but the allocation of funds for building maintenance is still not sufficient, because it depends on the allocation of funds available from the ministry. It is expect to The LPMP of Aceh Province to pay more attention to the building maintenance and perform routine maintenance.